Changes in total knee arthroplasty design affect in-vivo kinematics in a redesigned total knee system: A fluoroscopy study. (May 2018) - Zambianchi, Francesco; Fiacchi, Francesco; Lombari, Vincenzo; Venturelli, Luca; Marcovigi, Andrea; Giorgini, Andrea; Catani, Fabio
Abstract: Background: Journey II Bi-Cruciate-Stabilized knee system was designed to overcome the complications of Journey Bi-Cruciate-Stabilized, including ilio-tibial band inflammation and episodes of dislocation. The purpose of this study was to assess differences in knee kinematics between the first and second-generation design by means of video-fluoroscopy. Re -designed prosthesis in-vivo kinematics was analyzed during activities of daily living and results were eventually compared with those of the previous system, as reported in a previously published study. It was hypothesized that changes in components' design influences replaced knee's kinematic patterns. Methods: Sixteen patients (3 males, 13 females) implanted with the redesigned prosthesis were assessed by video-fluoroscopy during stair-climbing, chair-rising and leg-extension at 8 months of follow-up. Patterns of axial rotation and antero-posterior motion of the medial and lateral femoral condyles were obtained. Range of Motion and International Knee Society Score were recorded pre- and post-operatively. Student t -tests were applied to compare the mean of each interesting variables. Findings: The comparison of the kinematics of the two designs revealed similar patterns of axial rotation, with progressive femoral external rotation in flexion and reduced absolute values of displacement for the new system. Reduced posterior displacements of the medial and lateral condyles were observed in Journey II patients. In terms of absolute location, the lateral condyle in the redesigned prosthesis showed a more anterior position on the tibial-baseplate embedded coordinate system at maximal flexion. Interpretation: Design changes in the recently-introduced total knee system contributed to modify its in-vivo knee kinematics as demonstrated by video-fluoroscopy. Highlights: Total knee arthroplasty kinematics of two systems was analyzed by means of fluoroscopy. Comparison includes 16 new total knee designs and 16 old systems, as described in a previous study. Similar patterns of knee axial rotation were described between the two total knee systems. As proposed, the new system obtained reduced medial and lateral displacement compared to the old. Design changes in the redesigned prosthesis contributed to modify its in-vivo knee kinematics.